Implementasi Framework Laravel pada Sistem Manajemen Penomoran dan Arsip Surat Bawaslu Kota Surabaya - Lailatul Fitria; Umi Chotijah (STIKes Ibnu Sina Ajibarang, 2024)
Of course, in every government there must be an administrative part, where this part plays an important role in the management of government administration. One of the government institutions that are always tied to administrative affairs is Bawaslu Surabaya. Bawaslu acts as a state agency responsible for managing correspondence documents and election-related information. Starting from the submission of correspondence to the Mail archive, everything is part of the sub. HR Bawaslu. However, due to the storage and arrangement of files that are still manual, making it difficult to determine the numbering of letters to be worked on, or search for incoming and outgoing files that have been archived. Therefore, in this study will be a solution to overcome these problems by building a numbering and archive management system using the Laravel framework. Laravel Framework has its own advantages such as, easy to develop, faster performance, data security, data reload more stable, and much more. So Laravel can be an efficient and effective solution for developers in building powerful, large-scale, and easy-to-develop web applications.